The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
CHI '12 Extended Abstracts on Human Factors in Computing Systems 2012
DOI: 10.1145/2212776.2223802
|View full text |Cite
|
Sign up to set email alerts
|

Feel

Abstract: This work proposes a system for the automatic annotation and monitoring of cell phone activity and stress responses of users. While mobile phone applications (e.g., e-mail, voice, calendar) are used to non-intrusively extract the context of social interactions, a non-intrusive and comfortable biosensor is used to measure the electrodermal activity (EDA). Then, custom stress recognition software analyses the streams of data in real-time and associates stress levels to each event. Both contextual data and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…One approach treats it as a feature for objective detection of arousal, stress, or human emotion; systems in this approach typically attempt at detecting arousal states with some degree of accuracy. An example is the FEEL [1] system that uses triggers from mobile phone communications (such as receiving an SMS or an email) to record skin conductance and detect a stress level. Stress levels are then presented to users in a calendar or list view associated with the events that triggered them.…”
Section: Skin Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…One approach treats it as a feature for objective detection of arousal, stress, or human emotion; systems in this approach typically attempt at detecting arousal states with some degree of accuracy. An example is the FEEL [1] system that uses triggers from mobile phone communications (such as receiving an SMS or an email) to record skin conductance and detect a stress level. Stress levels are then presented to users in a calendar or list view associated with the events that triggered them.…”
Section: Skin Conductancementioning
confidence: 99%
“…Stress levels are then presented to users in a calendar or list view associated with the events that triggered them. Another approach requires users to make their own inferences based on skin conductance, providing instead clues for assisting interpretation [1,5]. Particularly relevant to us are the systems that reflect long-term trends of skin conductance in everyday life.…”
Section: Skin Conductancementioning
confidence: 99%
“…As a result, the application areas of affective [13] or biosensing wearables expand from medical monitoring to personal information applications (cf., Quantified Self 1 movement). Research has taken up on this development and focused on exploiting wearables to extract accurate information from the body's raw signals to provide value for users [1,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, researchers explored user preferences for using wearables in different contexts [2,11]. While the design space of biometric and affective wearables 1 http://quantifiedself.com/ includes many dimensions, we chose to focus in this part of our research on identifying potential user needs with regard to aspects of utility, connectivity, and feedback of the new biometric and affective wearables. We aim to understand user interest in acquiring and sharing biometric and emotional information, as well as exploring new channels and modalities for presenting this information.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that participants found the interface useful and could "reason forward and backward in time about their emotional experiences" (McDuff et al, 2012). Meanwhile, FEEL (Ayzenberg et al, 2012) is a lifelogging system that measures EDA, via a wristworn commercial sensor, and captures mobile phone data to determine the context of social interactions. The data is analysed in real-time to associate stress (via EDA) with events captured via the mobile phone (e.g.…”
Section: Wearable Sensors and Lifelogging Technologymentioning
confidence: 99%